2018
DOI: 10.3390/met8110953
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Two-Stage Cold Forging for a Drive Shaft with Internal Spline and Spur Gear Geometries

Abstract: A two-stage cold forging process was proposed to manufacture a drive shaft with an internal spline and spur gear geometries, and this process was mainly composed of a forward extrusion for preform and a forward-backward extrusion for the drive shaft. In the process design, the preform was designed using a volume apportioning scheme from the required target shape, thereafter, the initial round billet was outlined. AISI 1035 carbon steel was selected as the raw material, and a spheroidizing heat treatment was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Based on the prior results related to the systematic approach to the process design for a drive shaft [17], in order to substantialize the drive shaft using the combined cold extrusion, parametric investigations focusing on the shoulder angle on each extrusion die were conducted and compliance evaluations on the dimensional specifications were carried out, then the appropriate combination of the process parameters was extracted in this study. Here, two shoulder angles of θ 1 on the extrusion die for the preform forging and θ 2 on that for the combined extrusion were selected as the main geometric variables.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the prior results related to the systematic approach to the process design for a drive shaft [17], in order to substantialize the drive shaft using the combined cold extrusion, parametric investigations focusing on the shoulder angle on each extrusion die were conducted and compliance evaluations on the dimensional specifications were carried out, then the appropriate combination of the process parameters was extracted in this study. Here, two shoulder angles of θ 1 on the extrusion die for the preform forging and θ 2 on that for the combined extrusion were selected as the main geometric variables.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 a presents a sequential flow of the two-stage cold forging process used to produce the drive shaft, in which an internal spline with an irregular hexadecagonal cross-section and a sixteen-tooth spur gear were merged into a single metal member along a neutral axis. It can be seen that the round-type initial billet is shaped to the preform through the cold forward extrusion, and the preform is again deformed through the cold combined extrusion, which is defined as a forward–backward forging process, to obtain the cold forged drive shaft [ 25 , 26 , 27 ]. Given that the preform fabrication is the main object of this study, the subspecialized process flow is illustrated in Figure 1 b.…”
Section: Microstructural Characteristics and Mechanical Propertiesmentioning
confidence: 99%
“…In other words, considering that the two-stage cold forging process for producing the drive shaft is carried out continuously, it is also desirable to keep the FE models for the numerical simulations to maintain the same symmetric condition. Consequently, a one-sixteenth planar symmetric FE model for the cold forward extrusion was adopted for the forging punch and the extrusion die, as well as for the initial billet [ 25 , 26 , 27 , 28 ]. Figure 7 a depicts the three-dimensional FE models and the numerical simulation steps of the cold forward extrusion in order to visualize the preform.…”
Section: Numerical Simulations Of Cold Forward Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Deng et al, [5], a sound 3D rigid-plastic FE model of cold rotary forging of a 20CrMnTi alloy spur bevel gear has established utilizing the DEFORM-3D code and showed that it could be an effective tool in forging analyses. Ku [6] proposed a two stage cold forging for drive shaft with a forward extrusion for preform. The results indicated that the method could be well used to the production f drive shaft.…”
Section: Introductionmentioning
confidence: 99%